2013
DOI: 10.1109/tbme.2013.2270283
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid BCI System Combining P300 and SSVEP and Its Application to Wheelchair Control

Abstract: In this paper, a hybrid brain-computer interface (BCI) system combining P300 and steady-state visual evoked potential (SSVEP) is proposed to improve the performance of asynchronous control. The four groups of flickering buttons were set in the graphical user interface. Each group contained one large button in the center and eight small buttons around it, all of which flashed at a fixed frequency (e.g., 7.5 Hz) to evoke SSVEP. At the same time, the four large buttons of the four groups were intensified through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(126 citation statements)
references
References 34 publications
0
113
0
Order By: Relevance
“…Naseer et al (2014) have shown binary decision decoding for rehabilitation, whereas in this research the four control commands can be associated to four different decisions. Moreover, the previous hybrid EEG based researches for rehabilitation have shown the use of P300 and steady state visual evoked potentials (Li et al, 2013; Xu et al, 2013) to generate four control commands based on reactive tasks. As motor imagery and motor execution activate the same brain area (Beisteiner et al, 1995; Porro et al, 1996), the same goal can be achived by this research using active tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Naseer et al (2014) have shown binary decision decoding for rehabilitation, whereas in this research the four control commands can be associated to four different decisions. Moreover, the previous hybrid EEG based researches for rehabilitation have shown the use of P300 and steady state visual evoked potentials (Li et al, 2013; Xu et al, 2013) to generate four control commands based on reactive tasks. As motor imagery and motor execution activate the same brain area (Beisteiner et al, 1995; Porro et al, 1996), the same goal can be achived by this research using active tasks.…”
Section: Discussionmentioning
confidence: 99%
“…BMIs have been proposed for motor neurorehabilitation, motor replacement and assistive technologies (de Almeida Ribeiro et al, 2013), and wheelchair control (Li et al, 2013). Previous work by RamosMurguialday et al (2013) with chronic (post 2 weeks) stroke patients showed that patients using-BMIs recovered a wider range of movements than the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, hybrid EEG-based BCI has been developed using the combination of different mental strategies [41]. Currently, most of the hybrid EEG-based BCIs use the combination of motor imagery with SSVEP [40] and P300 with SSVEP [4245]. …”
Section: Introductionmentioning
confidence: 99%